Biological Activities of the Compounds Bearing 1,3,4-Oxa(thia)diazole Ring: A Review - Franski, Rafal (Asian Journal of Chemistry, 2016)
Recent literature concerning the antibacterial, antiinflammatory, antituberculosis, anticancer, anticonvulsant, insecticidal, fungicidal, herbicidal and other biological activities of organic compounds containing 1,3,4-oxa(thia)diazole ring has been summarized.